ANALISIS RESPON MASYARAKAT PADA PLATFORM MEDIA SOSIAL TWITTER TERHADAP TOKOH POLITIK, JENDERAL TNI (PURN.) GATOT NURMANTYO - Rahmasari, Gina; Andini, Rizkiki (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Gatot Nurmantyo is the 19th TNI Commander, who began to become a topic of conversation among Indonesians, in connection with his presence in public giving a statement regarding himself who was also offered to participate in the KLB as the general chairman of the Democratic Party replacing AHY. Twitter is a digital communication platform that also participates in discussing politics. Various kinds of opinions expressed by twitter users are classified into three types of opinion using Text Mining and Naive Bayes methods as classifier. The three types of opinions are classified into positive opinions, negative opinions, and neutral opinions. Based on 300 data taken, the results of the classification of opinions obtained are 24.67% containing positive opinions, 53.33% neutral opinions, and 22% negative opinions with the level of confidence of training results is 65%.